2012
DOI: 10.4052/tigg.24.112
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Sialidase Activity and the Role of Sialidase in the Brain

Abstract: Sialic acid is an acidic monosaccaride and plays crucial roles in various membrane functions in mammalian central nervous systems. Sialidase removes sialic acid from sialoglycoconjugates and also plays crucial roles in many neural functions, including differentiation and maturation of neurons and learning and memory. Recently, we visualized extracellular sialidase activity on the membrane surface in the rat brain by using a highly sensitive fluorescent histochemical method. Myelin-abundant regions showed inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Neu4 catalyzes degradation of PSA as well as removal of sialic acid from glycoproteins, gangliosides, and oligosaccharides (26,27,30). PSA plays an important role in hippocampal synaptic plasticity and memory (2,3,6). In hippocampal MFs, the expression level of PSA on NCAM is related to synaptic maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Neu4 catalyzes degradation of PSA as well as removal of sialic acid from glycoproteins, gangliosides, and oligosaccharides (26,27,30). PSA plays an important role in hippocampal synaptic plasticity and memory (2,3,6). In hippocampal MFs, the expression level of PSA on NCAM is related to synaptic maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In the hippocampus, it has been reported that sialyl signalling via gangliosides such as GQ1b and PSA, which bind to neural cell adhesion molecule (NCAM), is necessary for synaptic plasticity and memory [ 33 , 34 , 35 ]. Sialidase also plays important roles in many neural functions, including neural excitation, axonal elongation, differentiation and maturation [ 5 , 36 ]. Four types of mammalian sialidase (Neu1, Neu2, Neu3 and Neu4) have been identified in mammalian tissues by their localization and enzymatic properties.…”
Section: Discussionmentioning
confidence: 99%
“…The two most prevalent species of sialic acids existing in nature are N -acetylneuraminic acid (Neu5Ac) and N -glycolylneuraminic acid (Neu5Gc) [ 1 , 2 , 3 ]. Neu5Ac is abundantly contained in the mammalian brain and plays crucial roles in many neural functions such as memory, synaptic plasticity, brain development and neurological disorder [ 4 , 5 , 6 ]. In contrast, Neu5Gc is synthesized via the effect of cytidine monophospho- N -acetylneuraminic acid hydroxylase (CMAH), which catalyzes the conversion of cytidine 5'-monophosphate Neu5Ac (CMP-Neu5Ac) to CMP-Neu5Gc [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We developed novel fluorescent sialidase substrates for histochemical staining of sialidase activities in mammalian tissues. Since sialidase plays crucial roles in many biological functions including lysosomal catabolism, immune system and neural functions [2] , [31] , BTP-Neu5Ac is a powerful tool for detailed investigation of sialidase functions. Since the cytotoxicities of BTP-Neu5Ac and BTP were undetectable, BTP-Neu5Ac can be used for biological assay of sialidase in the living tissue, e.g.…”
Section: Discussionmentioning
confidence: 99%